Sosialisasi Pemanfaatan Pembukuan Digital Pada Kelompok UMKM Desa Sait Buttu Saribu - Suci Puspita Sari; Ahmad Afandi (Jurnal Nusantara Berbakti, 2023)
Being an MSME actor definitely requires good financial management so that income and expenses can be recorded systematically. The results of the research conducted show that there are still many MSMEs in Sait Buttu Saribu Village who still use manual financial bookkeeping records. And quite a few of them often miscalculate their balances or their financial records in the form of paper or books are lost and scattered. Without this socialization and workshop, people will continue to use manual methods and experience problems with calculation errors that make balances unbalanced or incorrect. This outreach aims to provide education and insight to MSME players, especially in Sait Buttu Saribu Village, so that it is easier to use digital applications for bookkeeping their business finances. There were around 20 participants who took part in this socialization and workshop. And during the event, people were very enthusiastic about asking about digital bookkeeping. Which means that in this village there are still many who don't understand digital financial bookkeeping.